PHYSIOLOGICAL FUNCTIONS OF THE HEART AND THEIR PATHOLOGICAL ALTERATIONS: CLINICAL SIGNIFICANCE AND DIAGNOSTIC OPPORTUNITIES - Ashuraliyeva Shaxnoza Ulug‘bek qizi (Innovate Conferences, 2025)
Cardiovascular diseases remain the leading cause of death worldwide, representing a major public health challenge. This article provides an in-depth overview of the physiological functions of the heart and their pathological alterations. Modern diagnostic opportunities, including electrocardiography, echocardiography, magnetic resonance imaging, biomarkers, and the application of artificial intelligence technologies in clinical practice, are discussed. The findings highlight the significance of studying cardiac function in detail for early diagnosis, prevention of severe outcomes, and improvement of treatment effectiveness.
Keywords: cardiac physiology, pathological alterations, cardiovascular diseases, diagnostics, artificial intelligence